Meningkatka Kemampuan Literasi Membaca Al-Qur’an melalui Tradisi Budaya Literasi di Taman Pendidikan Qur’an Nurul Ikhlas Sawah Besar Jakarta Pusat, Provinsi DKI Jakarta - Ika Kartika; Yanti Hasbian Setiawati; Saepudin Saepudin; Aman Sunasa; Nova Dahliah Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Nurul Ikhlas Qur'an Education Park is located on Jalan Dwi Warna IV RT. 003/RW 009, Sawah Besar District, Central Jakarta DKI Jakarta Province, was established in 1990 which was built on a 90 meter plot of land. Nurul Ikhlas Qur'an Education Park is a religious institution whose focus is on memorizing the Qur'an. The method used in community service activities is to provide guidance to teachers and student guardians in developing literacy cultural traditions. The media used in coaching teachers is by application. After coaching about the process of Al-Qur'an Literacy Culture in Improving Al-Qur'an Reading Ability in Qur'an Education Parks using 2 stages, namely the guidance stage of habituation and development. As for the evaluation of students given assignments at home. Factors that support literacy activities are awareness in students and motivation given by teachers/parents to encourage students' interest in reading. Meanwhile, the factors that hinder literacy are students' lack of interest in reading, the family environment and during this pandemic the teacher cannot monitor directly.